Effects of the European Union agricultural and environmental policies in the sustainable of most common mediterranean soils - Nunes, José Manuel Rato (2017)
Agro-environmental measures promoted by the European Union focus mainly on environmental protection by maintaining sustainable levels of productivity that are adequate to the agro-ecological conditions of each region on different Member States. Among these European Union promoted measures the one known as “Extensive Forage Systems” is particularly relevant for the Mediterranean Region. In order to analyze the impact of this measure and to verify if the high expenditure of communitarian funds, with its implementation in Mediterranean soils, is aligned with the predicted benefits, a seven-year study in a southern Portugal region was conducted. In this regard, several soil chemical parameters such as organic matter, pH, electrical conductivity, “available” phosphorus, “available” potassium and heavy metal levels (Cd, Cr, Cu, Zn, Mn, Pb and Ni), were assessed, in 1329 different plots in order to represent some of the existing diversity of the Mediterranean environment, identified by the Portuguese Parcel Identification System, and considering the possibility to evaluate the evolution of these parameters on the main soil types of the region. The obtained results enabled us to verify that the application of the agro-environmental measure “Extensive Forage Systems” did not lead, during the 7 years of the study, to any significant change in terms of organic matter, soil pH and/or heavy metals content. Still it contributed for a small growth on “available” phosphorus and potassium levels and to a significant increase on Soil electrical conductivity (EC). As a final conclusion we can refer that the application of the agro-environmental measure “Extensive Forage Systems”, in soil, clime and cultural conditions prevailing in this study (Typical Mediterranean conditions from the South of Europe), did not reach its main objective, which was to increase the organic matter content in soils